A secret brotherhood? The question of black Freemasonry before and after the Haitian Revolution. Issue 3 (3rd July 2019) - Garrigus, John
ABSTRACT: Late eighteenth-century Saint-Domingue produced both a thriving Masonic movement and the most successful slave uprising in modern world history. Scholars have suggested but never proven that these two movements were linked. One biographer hypothesizes that white planters who knew the future Toussaint Louverture from colonial Masonic circles helped him organize the slave uprising of August 1791. This speculation is inspired by the fact that in the late 1790s Louverture signed his name with a distinctive pattern of dots. Many colonists and free men of color used similar symbols, which have been described as Masonic signatures. This article examines whether the approximately 300 men of all races who made such signatures in the 1780s and early 1790s were Masons. It finds little or no evidence that they were. It hypothesizes that men used these symbols to suggest their membership in secret societies that did not, in fact, exist.